Conserved Genome Organization and Core Transcriptome of the Lactobacillus acidophilus Complex - Crawley, Alexandra B.; Barrangou, Rodolphe (Frontiers in Microbiology, 2018)
The Lactobacillus genus encompasses a genetically and functionally diverse group of species, and contains many strains widely formulated in the human food supply chain as probiotics and starter cultures. Within this genetically expansive group, there are several distinct clades that have high levels of homology, one of which is the Lactobacillus acidophilus group. Of the uniting features, small genomes, low GC content, adaptation to dairy environments, and fastidious growth requirements, are some of the most defining characteristics of this group. To better understand what truly links and defines this clade, we sought to characterize the genomic organization and content of the genomes of several members of this group. Through core genome analysis we explored the synteny and intrinsic genetic underpinnings of the L. acidophilus clade, and observed key features related to the evolution and adaptation of these organisms. While genetic content is able to provide a large map of the potential of each organism, it does not always reflect their functionality. Through transcriptomic data we inferred the core transcriptome of the L. acidophilus complex to better define the true metabolic capabilities that unite this clade. Using this approach we have identified seven small ORFs that are both highly conserved and transcribed in diverse members of this clade and could be potential novel small peptide or untranslated RNA regulators. Overall, our results reveal the core features of the L. acidophilus complex and open new avenues for the enhancement and formulation and of next generation probiotics and starter cultures.